2019
DOI: 10.1002/jcp.28433
|View full text |Cite
|
Sign up to set email alerts
|

High cholesterol inhibits tendon‐related gene expressions in tendon‐derived stem cells through reactive oxygen species‐activated nuclear factor‐κB signaling

Abstract: Clinical studies have indicated that increased serum cholesterol levels raised the risk of tendinopathy in hypercholesterolemia, but the effect of cholesterol on tendon‐derived stem cells (TDSCs) and its underlying mechanism have not been studied. The purpose of this study is to investigate the association between cholesterol and tendinopathy in vitro and in vivo, and its underlying molecular mechanism as well. In TDSCs, the effect of cholesterol was assessed by quantitative polymerase chain reaction, western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 40 publications
4
21
0
1
Order By: Relevance
“…On the other hand, an important finding of the current study was that SFO-HF demonstrated a decrease of proteins involved in tendon remodeling when compared with SFO-C group. Our results corroborate with transcriptome study which demonstrated that ApoE −/− associated with HF diet, promotes mRNA-level dysregulation of signaling pathways related with ECM synthesis, and repair in the tendon, suggesting mechanism of hypercholesterolemia-induced tendinopathy (Li et al, 2019). TGF-β superfamily orchestrates essential cellular processes that include proliferation, differentiation, and growth of the ECM (Klein et al, 2002).…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, an important finding of the current study was that SFO-HF demonstrated a decrease of proteins involved in tendon remodeling when compared with SFO-C group. Our results corroborate with transcriptome study which demonstrated that ApoE −/− associated with HF diet, promotes mRNA-level dysregulation of signaling pathways related with ECM synthesis, and repair in the tendon, suggesting mechanism of hypercholesterolemia-induced tendinopathy (Li et al, 2019). TGF-β superfamily orchestrates essential cellular processes that include proliferation, differentiation, and growth of the ECM (Klein et al, 2002).…”
Section: Discussionsupporting
confidence: 88%
“…The viability and tenogenic differentiation of TDSCs are closely associated with the maintenance of the tendon microenvironment and the development of tendinopathy [8]. Because tendinopathy is closely correlated with hypercholesterolemia, we found that high cholesterol inhibits tendon-related gene expression in TDSCs [11]. However, the effect of cholesterol on the viability of TDSCs remains unknown.…”
Section: Introductionmentioning
confidence: 83%
“…Western blotting was performed based on a previously described protocol [11]. After the indicated stimulation, proteins from TDSCs were extracted with RIPA buffer containing PMSF, and protease and phosphatase inhibitor cocktails.…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Например, высокий уровень холестерина у мышей, активируя передачу сигналов по каскаду NF-κB, ингибирует экспрессию генов синтеза соединительной ткани в стволовых клетках сухожилий. У мышей, в рационе которых было значительное содержание насыщенных жиров, высокий уровень хо-лестерина увеличивал концентрацию АФК, снижал экспрессию коллагена 1 и теномодулина [30].…”
unclassified